Proline catalyzed enantioselective synthesis of (2S,3S)-3-hydroxypipecolic acid and formal synthesis of (+)-swainsonine - Aher, Ravindra D.; Sudalai, Arumugam (Tetrahedron Letters, 2016)
A short enantioselective synthesis of (2S,3S)-3-hydroxypipecolic acid (overall yield: 18.8%; 96% ee) and formal synthesis of (+)-swainsonine (overall yield: 13.6%; 96% ee) have been described starting from commercially available acrolein. The synthetic strategy involves a high enantioselective L-proline catalyzed sequential c-amination and diastereoselective (dr > 99:1) Barbier allylation of aldehyde in one-pot as the key reaction. (C) 2016 Elsevier Ltd. All rights reserved.